2003
DOI: 10.1038/sj.ijo.0802260
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic syndrome is associated with elevated circulating C-reactive protein in healthy reference range, a systemic low-grade inflammatory state

Abstract: OBJECTIVE:To elucidate the underlying mechanisms between C-reactive protein (CRP) and cardiovascular disease, we examined the association of circulating CRP in healthy reference range (r1.0 mg/dl) measured by high-sensitive CRP assay with the metabolic syndrome (MS). DESIGN: Cross-sectional study of circulating CRP in adult men. SUBJECTS: A total of 3692 Japanese men aged 34-69 y. MEASUREMENTS: Serum CRP, total cholesterol, triglycerides, LDL-cholesterol, fasting glucose, fasting insulin, uric acid, systolic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
147
2
7

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(167 citation statements)
references
References 39 publications
11
147
2
7
Order By: Relevance
“…These results are in agreement with several previous studies [12][13][14][15]. Low grade systemic inflammation as evidenced by high levels of hsCRP is suggested to be one of the mechanisms by which known risk factors such as obesity, smoking and hypertension promote the development of T2DM [1,16].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with several previous studies [12][13][14][15]. Low grade systemic inflammation as evidenced by high levels of hsCRP is suggested to be one of the mechanisms by which known risk factors such as obesity, smoking and hypertension promote the development of T2DM [1,16].…”
Section: Discussionsupporting
confidence: 93%
“…High CRP levels also correlate well with other parameters of MS [10]. Majority of the previous studies showing raised CRP levels in obese children are from the developed countries [4][5][6][7][8][9][11][12][13][14]. The need to generate data from the developing countries is even more in view of the recent observations and recommendations for diagnosis of obesity and MS for Asian Indians [15].…”
Section: Introductionmentioning
confidence: 99%
“…With every 1 kg/m 2 increase in BMI, odds of high hsCRP level were increased by 37% (multivariate OR 1.37, 95% CI 1.23-1.53, p-value <0.0001). Obesity related metabolic syndrome is associated with increase in the levels of a number of markers of inflammation especially CRP [4][5][6]. This subclinical or low grade inflammatory state in simple obesity is associated with increased risk for cardiovascular disease and diabetes [8][9][10].…”
Section: Correlation Between Hscrp and Other Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Several recent studies also suggest that a proinflammatory state and endothelial dysfunction also associate with the metabolic syndrome. [5][6][7][8][9][10] We have recently shown that subjects with the metabolic syndrome had increased prevalence of erectile dysfunction (ED) (26.7 vs 13%, P ¼ 0.03); moreover, there was an increase in ED prevalence (International Index of Erectile Function, IIEF o21) as the number of components of the metabolic syndrome increased, suggesting that the cumulative burden of cardiovascular risk may be central to the pathogenesis of ED. 11 Mediterranean-style diet rich in whole grain, fruits, vegetables, legumes, walnut, and olive oil might be effective in reducing both the prevalence of the metabolic syndrome and the cardiovascular risk associated with.…”
Section: Introductionmentioning
confidence: 99%